Gas Embolism During Hysteroscopic Surgery?: Three Cases and a Literature Review. Issue 5 (1st September 2017) - Storm, Benjamin S.; Andreasen, Stine; Hovland, Anders; Nielsen, Erik W.
Abstract : During a period of 1 month, 3 episodes of probable or actual venous air embolism occurred during hysteroscopic surgery. All patients developed the same symptoms of ventilatory and hemodynamic decompensation, beginning with a reduction in end-tidal carbon dioxide, arterial desaturation, and cyanosis on the upper trunk, and rapidly progressed to hypotension and 2 cardiac arrests. While entrainment of some air is common during hysteroscopy, life-threatening embolism is a rare but serious complication for which an anesthetist needs to be vigilant and prepared. If even a small drop in end-tidal carbon dioxide occurs, venous air embolism should be suspected and the operation should be discontinued. Abstract : Supplemental Digital Content is available in the text.